Pengaruh Lama Merokok Terhadap Gangguan Kognitif pada PopuIasi Lansia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Background: Cognitivedisorder could affect quite complicatedsocialproblems, since inability ofbrainfimction that develop. There are controversies around the effects of smoking in cognitive impairment in elderly. Objective: to assess the proportion of cognitive impairment in smoking elderly population. To measure the odds ration of smoking effect in cognitive impairment in elderly. Methods: apopulation based matched case control study with the setting in Gondokusumansubdistrict, Jogjakarta. Subjects are male individuals with age of e" 60 years old, smoker or nonsmoker with cognitive impairment, measured with Mini Mental State Examination (MMSE) adjusted with age and educational level. The size of sample was calculated according to Lemeshow, with level of significance of95% and strength of80%. 152 subjects were required in this study. Statistical analysis was done with SPSS. Results: there was a significant results in the duration of smoking, p= 0,019 (95% Cll.i5-4,27) OR 3,33 and smoking> 20 cigarettes in one day, p= 0,025 (95% Cll, 14-8, 4 7) OR 3, lOin the incidence of cognitive impairment in elderly population. Keywords: smoking, cognitive impairment, riskfactor, addiction, elderly